A Novel Laboratory-Scale Mesocosm Setup to Study Methane Emission Mitigation by Sphagnum Mosses and Associated Methanotrophs - Kox, Martine A. R.; Smolders, Alfons J. P.; Speth, Daan R.; Lamers, Leon P. M.; Op den Camp, Huub J. M.; Jetten, Mike S. M.; van Kessel, Maartje A. H. J. (Frontiers in Microbiology, 2021)
Degraded peatlands are often rewetted to prevent oxidation of the peat, which reduces CO2 emission. However, the created anoxic conditions will boost methane (CH4) production and thus emission. Here, we show that submerged Sphagnum peat mosses in rewetted-submerged peatlands can reduce CH4 emission from peatlands with 93%. We were able to mimic the field situation in the laboratory by using a novel mesocosm set-up. By combining these with 16S rRNA gene amplicon sequencing and qPCR analysis of the pmoA and mmoX genes, we showed that submerged Sphagnum mosses act as a niche for CH4 oxidizing bacteria. The tight association between Sphagnum peat mosses and methane oxidizing bacteria (MOB) significantly reduces CH4 emissions by peatlands and can be studied in more detail in the mesocosm setup developed in this study.